Pharmacokinetic drug interactions of the non-vitamin K antagonist oral anticoagulants (NOACs). (September 2018) - Gelosa, Paolo; Castiglioni, Laura; Tenconi, Marco; Baldessin, Ludovico; Racagni, Giorgio; Corsini, Alberto; Bellosta, Stefano
Graphical abstract: Abstract: The use of warfarin, the most commonly prescribed oral anticoagulant, is being questioned by clinicians worldwide due to warfarin several limitations (a limited therapeutic window and significant variability in dose-response among individuals, in addition to a potential for drug-drug interactions). Therefore, the need for non-vitamin K antagonist oral anticoagulants (NOACs) with a rapid onset of antithrombotic effects and a predictable pharmacokinetic (PK) and pharmacodynamic (PD) profile led to the approval of five new drugs: the direct factor Xa (F-Xa) inhibitors rivaroxaban, apixaban, edoxaban and betrixaban (newly approved by FDA) and the direct thrombin (factor-IIa) inhibitor dabigatran etexilate. The advantages of NOACs over warfarin are a fixed-dosage, the absence of the need for drug monitoring for changes in anti-coagulation and fewer clinically significant PK and PD drug–drug interactions. NOACs exposure will likely be increased by the administration of strong P-glycoprotein (P-gp) and cytochrome P450 (CYP) 3A4-inhibitors and may increase the risk of bleeds. On the contrary, P-gp inducers could significantly decrease the NOACs plasma concentration with an associated reduction in their anticoagulant effects. This manuscript gives an overview of NOACs PK profiles and their drug-drug interactions potential. This is meant to be of help to physicians in choosing the best therapeutic approach for their patients.